Personality traits in musicians with different types of music performance anxiety - Spahn, Claudia; Krampe-Heni, Franziska; Hohagen, Jesper; Immerz, Anna; Nusseck, Manfred (Frontiers in Psychology, 2024)
Introduction This study investigated the relationship between personality traits and MPA in the course of a specific performance. Methods For this purpose, symptoms of MPA, functional coping with MPA and performance-related self-efficacy of a sample of 393 musicians including 23% professional, 49% non-professional orchestra musicians and 28% singers in amateur choirs were categorized and then used to analyze differences in the personality traits. The questionnaires used were the NEO-FFI and the PQM. Results The results showed that professional orchestra musicians had significantly higher openness and conscientiousness than non-professional orchestra musicians and amateur choir singers. Musicians who had few symptoms of MPA, positive coping with MPA and high self-efficacy across a specific performance (Type 1) have low neuroticism in their personality traits. Regarding MPA, the personality traits were correlated with all MPA scales after the performance but less with MPA scales before and during the performance. Discussion Results could indicate that personality traits play a particularly important role in the processing of performance experiences after the performance and suggest focusing on the situation after the performance in particular with professional orchestra musicians.